2012
DOI: 10.1002/chem.201202461
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Selective Spectroscopic Detection of Mercury(II) in Water by Using Pyridylporphyrin–DNA Conjugates

Abstract: Single-labeled pyridylporphyrin-DNA conjugates are reported as highly sensitive and selective spectroscopic sensors for mercury(II) ions in water. The effects of chemical structure (thymine versus adenine), number of nucleotides (monomer versus octamer), and porphyrin metalation (Zn versus free base) on the sensitivity and selectivity of mercury(II) detection are explored. The results indicated that pyridylporphyrin rather than the nucleobase plays a crucial role in mercury(II) sensing, because porphyrin conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In particular, Balaz and co-workers studied their dependency on the presence of thymine or adenine, the number of nucleobases, and the Por central metal. 198 Linking adenine instead of thymine produced a decrease in the limit of detection of Hg 2+ in water, while the combination of zinc as the central metal and oligodeoxythymidine as the sensing unit showed the best results toward this mercury cation. Cytosine-substituted Co(II)Por and Zn(II)Por have been used, on the other hand, as nucleotide receptors.…”
Section: Ps Biohybrids With Nucleobases Nucleosides and Nucleotidesmentioning
confidence: 99%
“…In particular, Balaz and co-workers studied their dependency on the presence of thymine or adenine, the number of nucleobases, and the Por central metal. 198 Linking adenine instead of thymine produced a decrease in the limit of detection of Hg 2+ in water, while the combination of zinc as the central metal and oligodeoxythymidine as the sensing unit showed the best results toward this mercury cation. Cytosine-substituted Co(II)Por and Zn(II)Por have been used, on the other hand, as nucleotide receptors.…”
Section: Ps Biohybrids With Nucleobases Nucleosides and Nucleotidesmentioning
confidence: 99%
“…Indeed, we note that porphyrin based materials have been used to selectively recognize a variety of different materials, including dopamine [39] and mercury(II) [40]. Sensors utilizing other polymers that undergo swelling can be envisaged to detect vapors such as chloroform [41] or ammonia [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, chemosensor studies based on porphyrin‐thymine conjugates have seldom been reported so far, although porphyrin is among the best known self‐associating dyes in poor solvents, and this self‐aggregation is clearly reflected by changes in the absorption spectra (Liu et al ., ; Arai and Segawa, ). In this regard, porphyrins and their derivatives represent very attractive components of molecular sensors due to the fact that porphyrins are highly flexible and a number of structural changes involving different central metal ions and peripheral substituents can be introduced, which in turn is reflected by changes in the emission and absorption spectra (Fang and Liu, , Yang et al ., , Choi et al ., , Bettini et al ., ). In general, porphyrins exhibit an intense and narrow absorption band in the visible spectrum between 400 and 460 nm as well as an emission band in the red part of the spectrum (550–750 nm) (Karolczak et al ., ).…”
Section: Introductionmentioning
confidence: 98%